The Effect of Bay Leaf (Syzygium polyanthum) Extract on The Hepatic Histopathology of Male White Rats (Rattus norvegicus) Induced by Ibuprofen - Dirganingrum, Kadek Galuh; Damanik , Efrisca M. Br.; Nugroho, Teguh Dwi; Deo, Dwita Anastasia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Excessive use of ibuprofen can trigger Drug Induced Liver Injury (DILI) through oxidative stress mechanisms. Syzygium polyanthum (bay leaf) contains antioxidant compounds with potential hepatoprotective activity. Objective to determine the effect of ethanol extract of bay leaves on the improvement of liver histopathology in ibuprofen-induced rats. This experimental study used 36 Sprague Dawley rats divided into six groups: Negative Control, two Positive Controls (ibuprofen induction), and treatment groups P1, P2, and P3 (ibuprofen induction + extract at doses of 50, 150, and 250 mg/kgBW). Histopathological changes were evaluated using the Manja Roenigk scoring system. Data were analysed using the Kruskal–Wallis test followed by Dunn’s Post Hoc test. There were significant differences among groups (p < 0.001). Group P3 (250 mg/kgBW) showed the lowest damage score (1.35 ± 0.15), approaching normal conditions, and differed significantly from P1 (2.37 ± 0.27), which showed the highest damage. Lower doses did not provide optimal improvement. Bay leaf extract significantly improved liver histopathology in ibuprofen-induced rats in a dose-dependent manner, with the most effective dose being 250 mg/kgBW.